233k views
4 votes
Solve the following SYS

y = 6x + 5
y= 4x - 11


This is the second question

2 Answers

6 votes

Answer:

x = -8 y = -43

Explanation:

y = 6x + 5

y= 4x - 11

6x + 5 = 4x - 11

2x = -16

x = -8

y = 4(-8) - 11

y = -32 - 11

y = -43

User HBomb
by
5.6k points
0 votes

Answer:

x=-8, y= -43

Explanation:

y = 6x + 5

y= 4x - 11

Since both equations are equal to y, we can set them equal to each other

6x + 5= 4x - 11

Subtract 4x from each side

6x-4x+5 = 4x-4x-11

2x+5 = -11

Subtract 5 from each side

2x+5-5 = -11-5

2x = -16

Divide each side by 2

2x/2 = -16/2

x = -8

Now we need to find y

y = 6x+5

y = 6(-8) +5

-48+5

-43

User Nathan Alard
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.